Green to gold : how smart companies use environmental strategy to innovate, create value, and build competitive advantage. - Esty, Daniel C., ....-; Winston, Andrew S., ....- (Hoboken : Wiley, 2009)
"Two experts from Yale tackle the business wake-up-call du jour-environmental responsibility-from every angle in this thorough, earnest guidebook: pragmatically, passionately, financially and historically. Though "no company the authors know of is on a truly long-term sustainable course," Esty and Winston label the forward-thinking, green-friendly (or at least green-acquainted) companies WaveMakers and set out to assess honestly their path toward environmental responsibility, and its impact on a company?s bottom line, customers, suppliers and reputation. Following the evolution of business attitudes toward environmental concerns, Esty and Winston offer a series of fascinating plays by corporations such as Wal-Mart, GE and Chiquita (Banana), the bad guys who made good, and the good guys-watchdogs and industry associations, mostly-working behind the scenes. A vast number of topics huddle beneath the umbrella of threats to the earth, and many get a thorough analysis here: from global warming to electronic waste "take-back" legislation to subsidizing sustainable seafood. For the responsible business leader, this volume provides plenty of (organic) food for thought. "